Vocabulary Learning Strategies In Learning English As A Foreign Language At SMA Negeri 1 Wonggeduku - Suharmin, Suharmin; Hanafi, Hilaluddin; Alberth, Alberth (Journal of Language Education and Educational Technology (JLEET), 2016)
The objectives of this study were: to obtain data about the variations of studentsâ€™ Vocabulary Learning Strategy (VLS) used in the SMA Negeri 1 Wonggeduku, to know the VLS that frequently used by the students and to obtain data of learning strategy differences based on gender. This study adopted a mix method design which employed both qualitative and quantitative research design. Instruments of the study were questionnaire and interview guideline. The study was conducted at SMA Negeri 1 Wonggeduku, involving students who 126 students participated in this study by filling out a questionnaire. Result of the study showed that All of the students were perform each strategy which is used in this research. However, in each strategy, they have their own preference such us in Determination strategy, they prefer to choose item 1 â€œ; I use a bilingual dictionary to help me translate words into English languageâ€ rather than the other item in Determination Strategy. In answering the second research question about the most frequently used strategy, it is revealed that the students in SMA Negeri 1 Wonggeduku prefer to choose Memory Strategy got the highest rank among the other six categories available, followed by Determination, Social (Discovery), Metacognitive, Social (Consolidation) and the last is Cognitive Strategy. In answering the last research question about the differences between Female and Male preference, the only differences happen in the order of their choice. They both agree in the order one to four (Memory, Determination, Social (Discovery) and Metacognitive). However, their differences come in the order five to six (between Social (Consolidation) and Cognitive Strategy).